Empathy and irrational beliefs imprisoned for crimes against the sexual freedom of a penitentiary institute in Lima East. - Lisseth Casariego More (2019)
Objective of the present investigation was to analyze the relationship between the variables ofempathy and irrational beliefs. Materials and methods: it is of non-experimental design, of crosssectionand correlational scope. The sample consisted of 127 inmates in a penitentiary institute inLima East, over 18 years of age, held for crimes against sexual freedom. The instruments used fordata collection were the Interpersonal Reactivity Scale (Davis, 1980) and the Registry of Opinions(Davis, McKay and Eshelman, 1987). Results showed that there is a significant inverse relationshipbetween empathy and the irrational beliefs of absolute competence and continuity of effects (p <0.05).However, no significant relationship was found between empathy and the irrational beliefs of affectionand approval, relativity of acts, social expectations and external control (p> 0.05). Conclussion: thatempathy is inversely linked to self-sufficiency generated by the belief of being absolutely competentand the inadequate coping of past experiences.